Differential activation of the renin-angiotensin-aldosterone-system in response to childhood and adulthood trauma. (September 2019) - Terock, Jan; Hannemann, Anke; Janowitz, Deborah; Van der Auwera, Sandra; Bahls, Martin; Völzke, Henry; Grabe, Hans J.
Highlights: Levels of renin and aldosterone were altered in relation to childhood and adulthood trauma in the general population. Exposure to and severity of childhood trauma were associated with increased levels of aldosterone. This association was carried by all dimensions of childhood abuse, but not neglect. Adulthood trauma and PTSD were associated with enhanced renin levels. Renin and aldosterone were increased in subjects with exposure to childhood and adulthood. Abstract: Objective: Previous evidence suggested lasting and cumulative effects of traumatization on the renin-angiotensin-aldosterone-system (RAAS). However, it is unclear whether traumas during childhood and those experienced in adulthood differentially impact the RAAS. In this study, we sought to investigate main and putative interactive effects of childhood and adulthood trauma on RAAS functioning. Methods: Plasma concentrations of renin and aldosterone were measured in a general population sample (n = 2016). Childhood trauma was assessed using the Childhood Trauma Questionnaire (CTQ), adulthood trauma was measured using the PTSD module of the Structured Clinical Interview of the DSM-IV. Linear regression models were calculated to assess the relations between childhood or adulthood traumatization with renin and aldosterone concentrations. Results: Exposure to (ß = 0.094; p = 0.01), severity of childhood trauma (ß = 0.004; p = 0.01) were associated with increased aldosterone, but not renin levels. Results were carried by all dimensions of abuse, while childhood neglect was not associated with altered RAAS activity. In contrast, adulthood traumas (ß = 0.113; p < 0.01) were significantly associated with increased renin concentrations. Subjects with PTSD (renin: ß = 0.345; p = 0.01; aldosterone: ß = 0.232; p = 0.04) and those who had been exposed to both childhood and adulthood trauma showed increases in renin (ß = 0.180; p < 0.01) and aldosterone (ß = 0.340; p < 0.01) levels. Discussion: These findings indicate that trauma is associated with differential alterations of the RAAS depending on the time of traumatization. Moreover, exposure to childhood or adulthood trauma may act synergistically on the RAAS, resulting in severe dysregulation of the RAAS. The results contribute to explain associations between trauma and enhanced risk for physical disease.